O metodzie anarchistycznej polityki w XIX wieku - Antonów, Radosław (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
In the nineteenth century, anarchism was perceived as a dangerous doctrine marked by evil, while anarchist activity was tantamount to chaos and, naturally, anarchy.During this period the terms ‘regicide’ and ‘nihilist’ were used interchangeably with the term ‘anarchist.’ The absolute animus against anarchy and anarchists was, most of all, a consequence of the violence used by anarchists in order to intimidate both the representatives of the ruling class and the society as a whole. Therefore, the method of anarchist politics consisted predominantly in propaganda of the deed, expressed by planned and executed attacks, revolutionary aspirations, and an open disdain for the state, the law, ownership, and prior social achievements. The positive side of the anarchist program went unnoticed in nineteenth-century societies, and was obscured by an uncompromising terrorist struggle led by anarchists against the state and its institutions. Nineteenth-century anarchists were the prototypes ofthe terrorists active at the turn of the twenty-first century.
Keywords: anarchizm; anarchiści; terroryzm; terroryści; nihilizm; nihiliści; zamach dynamitowy